2005
DOI: 10.1159/000086404
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Luteinizing Hormone and Follicle-Stimulating Hormone Expression during Ovarian Development and under Sexual Steroid Feedback in the European Eel

Abstract: Pituitary gonadotropins, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) are, in teleosts as in mammals, under the control of hypothalamic factors and steroid feedbacks. In teleosts, feedback regulations largely vary depending on species and physiological stage. In the present study the regulation of FSH and LH expression was investigated in the European eel, a fish of biological and phylogenetical interest as a representative of an early group of teleosts. The eel FSHβ subunit was cloned, sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 95 publications
4
41
0
1
Order By: Relevance
“…However, in European sea bass (Dicentrarchus labrax), glycoprotein-, FSH-, LH- mRNA increased simultaneously with the gonadosomatic index (GSI) during spermatogenesis (Mateos et al, 2003). In eel, FSH seems to mediate gonadotropin stimulation in the early stages of the gametogenesis, while LH seems to be involved in the end of gametogenesis (European eel: Aroua et al, 2005;Schmitz et al, 2005;Japanese eel: Jeng et al, 2007;Yoshiura et al, 1999).…”
Section: Pituitarymentioning
confidence: 99%
“…However, in European sea bass (Dicentrarchus labrax), glycoprotein-, FSH-, LH- mRNA increased simultaneously with the gonadosomatic index (GSI) during spermatogenesis (Mateos et al, 2003). In eel, FSH seems to mediate gonadotropin stimulation in the early stages of the gametogenesis, while LH seems to be involved in the end of gametogenesis (European eel: Aroua et al, 2005;Schmitz et al, 2005;Japanese eel: Jeng et al, 2007;Yoshiura et al, 1999).…”
Section: Pituitarymentioning
confidence: 99%
“…All of them have been sequenced in European eel (Querat et al, 1990a,b;Degani et al, 2003;Schmitz et al, 2005). In most teleosts, FSH regulates the first steps of the gonad maturation, while LH is involved in the final gonad development.…”
Section: Gonadotropinsmentioning
confidence: 99%
“…However, some researchers indicated that both gonadotropins are present in immature previtellogenic eels (Schmitz et al, 2005;Aroua et al, 2005).…”
Section: Gonadotropinsmentioning
confidence: 99%
See 2 more Smart Citations